Improving Mathematics Learning Outcomes with the Help of Teaching Aids In Grade VII Students - Wulan Lailatul Mufidah; Moh Syadidul Itqan; Nurul Isnaini (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Learning mathematics at the junior high school level often faces challenges, particularly in students’ low understanding of basic integer operations such as addition and subtraction. These difficulties frequently result in misconceptions and low learning outcomes because the material is abstract and is often taught using conventional methods without adequate learning support. Therefore, it is urgent to implement learning strategies that can make abstract mathematical concepts more concrete and meaningful for students. This research aims to improve learning outcomes and students' understanding of concepts in the material of integer addition and subtraction operations through the use of props. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, conducted in two cycles, each consisting of two meetings that include the stages of planning, action implementation, observation, and reflection. The subjects of this study were 32 seventh-grade students of MTsN 1 Probolinggo. The research instruments included learning outcome tests (pretest and posttest), student activity observation sheets, and documentation. The collected data were analyzed using descriptive quantitative analysis to examine improvements in learning outcomes from the pre-cycle to cycle II. The results showed a significant increase in student learning outcomes after the application of teaching aids. The average pretest score in the pre-cycle was 45%, which increased to 82.5% in the posttest of cycle I and further increased to 92.2% in the posttest of cycle II. The percentage of classical learning completeness also improved, from 18.75% in the pre-cycle to 87.5% in cycle I and reached 100% in cycle II. These findings indicate that the use of teaching aids helps students understand the concepts of integer addition and subtraction more concretely, facilitates problem-solving, and enhances learning outcomes. Thus, it can be concluded that the application of teaching aids is effective in improving conceptual understanding and mathematics learning outcomes of seventh-grade students at MTsN 1 Probolinggo.